Language, literacy, and pedagogy in postindustrial societies : the case of black academic underachievement - Mocombe, Paul.; Tomlin, Carol (New York : Routledge, 2013)
"In postindustrial economies such as the United States and Great Britain, the black/white achievement gap is perpetuated by an emphasis on language and language skills, with which black American and black British-Caribbean youths often struggle. This work analyzes the nature of educational pedagogy in the contemporary capitalist world-system under American hegemony. Mocombe and Tomlin interpret the role of education as an institutional or ideological apparatus for capitalist domination, and examine the sociolinguistic means or pedagogies by which global and local social actors are educated within the capitalist world-system to serve the needs of capital; i.e., capital accumulation. Two specific case studies, one in the United States and one in the United Kingdom, are utilized to demonstrate how contemporary educational emphasis on language and literacy parallels the organization of work and contributes to the debate on academic underachievement of black students vis-a-vis their white and Asian counterparts"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Blacks -- Education -- Case studies; African Americans -- Education -- Case studies; Blacks -- Education -- Great Britain -- Case studies; English language -- Social aspects -- United States -- Case studies; English language -- Social aspects -- Great Britain -- Case studies; Underachievement -- United States -- Case studies; Underachievement -- Great Britain -- Case studies; Electronic books